Analisis Kesalahan Siswa SMA dalam Menyelesaikan Soal Integral - Sindi Amelia; Gusri Yadrika (Universitas Batanghari Jambi, 2019)
The low achievement of students in completing integral questions must be responded by the teachers, because integrals are applicable material in various fields of science. By analyzing the types of student errors and knowing the location of student errors, it will be an evaluation for the teacher to overcome the students' mistakes in answering integral questions. The purpose of this study is to describe; (1) the types of student error in solving integral, (2) the causes of student errors in solving integral. This research method was a qualitative research. The research subjects were taken 10 students from MA Khairul Ummah Inhu. The results of the study indicated that; (1) There were 4 types of mistakes made by students, namely concept errors (36,7%), fact errors (3,3%), principle errors of (5%), and operation errors (20%); (2) A causes of errors was students did not understand the prerequisite material for the integral material. The suggestion to minimize students' mistakes in solving the problems is to provide an concept understanding of material that are prerequisites.